FRAMING OF SENTENCE COMPLEXITY IN EDITORIAL NEWS: CASE STUDY IN “THE JAKARTA POST AND KOMPAS - Syahrul Efendi Lubis; Zainuddin Zainuddin (Rahis Cendekia Indonesia, 2023)
This research is about Framing of Sentence Complexity in Editorial News: A Case Study in “The Jakarta Post and Kompas” using the topic of